Neurocognitive, social cognitive, and clinical predictors of creativity in schizophrenia. (October 2020) - Sampedro, Agurne; Peña, Javier; Ibarretxe-Bilbao, Naroa; Sánchez, Pedro; Iriarte-Yoller, Nagore; Pavón, Cristóbal; Hervella, Isabel; Tous-Espelosin, Mikel; Ojeda, Natalia
Abstract: Background: Creativity is considered an essential human accomplishment and a key component for daily life problem solving. It has been suggested that impairment in working memory, cognitive flexibility, and theory of mind could lead to lower creativity in schizophrenia. Additionally, other neurocognitive and social cognitive domains, as well as clinical symptoms could play a role in this relationship. However, the extent to which each of these domains influences creativity in schizophrenia remains unknown. Therefore, the aim of this study was to simultaneously investigate the specific contribution of neurocognitive, social cognitive, and clinical variables to creativity in schizophrenia. Methods: One hundred and one patients with schizophrenia were assessed in terms of sociodemographic, clinical, neurocognitive, social cognitive, and creativity variables. Results: After controlling for sociodemographic variables, regression analyses showed that higher social perception ( β  = 0.286, p  = .004) and processing speed ( β  = 0.219, p  = .023) predicted creativity total score. Higher social perception ( β  = 0.298, p  = .002) and processing speed ( β  = 0.277, p  = .004) explained figural creativity. Finally, lower negative symptoms ( β  = −0.302, p  = .002) and higher social perception ( β  = 0.210, p  = .029) predicted verbal creativity. Conclusions: Results suggest that neurocognitive, social cognitive, as well as clinical symptoms influence creativity of patients with schizophrenia. Moreover, these findings point out the prominent role of social cognition in creativity in schizophrenia.